PENGARUH IKLAN POLITIK DALAM PEMILIHAN ANGGOTA LEGISLATIF DI KECAMATAN MOTOLING BARAT KABUPATEN MINAHASA SELATAN - Ruru, Joorie (Sam Ratulangi University, 2015)
In Indonesia increasingly important political advertising used by politicians in local elections andpresidential elections, but also not free from controversy. Order to determine the effect of politicaladvertising in the election of legislators in South Minahasa Regency Motoling more specifically in thedistrict west.This type of research is the use of qualitative research, which is a type of research that is used toexamine the object in which the researcher is as. the number of respondents who becomes the object ofstudy is 50 peopleThe results showed political advertising in the legislative elections have considerable influence, in plainview of political advertising is a political force in communicating with the people who became theobject of political advertising.Keywords: Advertising Politics, Legislative Elections